Organizational justice, organizational reputation and self-esteem in improving employability in Malaysia / Hasnun Anip Bustaman, Mohammad Nazri Mohd Nor and Azni Zarina Taha - Bustaman, Hasnun Anip; Mohd Nor, Mohammad Nazri; Taha, Azni Zarina (UiTM Cawangan Johor, 2019)
This paper reviews the recent perspectives of the employability background in Malaysia, which lately has been gaining strong attention from the academicians. This paper begins by highlighting the Malaysian government who has undertaken various initiatives to improve Malaysia employment rate within the six months after graduation and yet, the rate has remained constant since the last five years. The situation even deteriorates due to the increased attitudes of the graduates who are choosy and refused to apply for a job after graduation. The traditional approaches are likely drowning in lifting the employment rate to the higher standard. Thus, this study highlights the employer's role as a new approach in dealing with the issue which has been discovered from the job seekers' perspectives. This study promotes the organizational justice, organizational reputation and self-esteem as the determinant factors to face a new trend amongst the graduate labours. The concept is an important characteristic to the outsiders such as the customers, stakeholders, co-workers, members of general public and others. As graduate labour is one of the outsiders to the organization, the concept anticipates to influence them in applying job with an organization, simultaneously improving the number of graduate's employability. To conclude, various parties have to cooperate with each other including the Malaysian government, higher education and employers for aspiration to improve the employment rate in the year 2020 as stipulated in RMK-11.